Neurophysiological correlates of various mental perspectives - Hinterberger, Thilo; Zlabinger, Milena; Blaser, Klaus (Frontiers in Human Neuroscience, 2014)
A common view of consciousness is that our mind presents emotions, experiences and images in an internal mental (re-)presentation space which in a state of wakefulness is triggered by the world outside. Consciousness can be defined as the observation of this inner mental space. We propose a new model, in which the state of the conscious observer is defined by the observer’s mental position and focus of attention. The mental position of the observer can either be within the mental self (intrapersonal space), in the mental outer world (extrapersonal space) or in an empathic connection, i.e. within the intrapersonal space of another person (perspective taking). The focus of attention can be directed towards the self or towards the outside world. This mental space model can help us to understand the patterns of relationships and interactions with other persons as they occur in social life. To investigate the neurophysiological correlates and discriminability of the different mental states, we conducted an EEG experiment measuring the brain activity of 16 subjects via 64 electrodes while they engaged in different mental positions (intrapersonal, extrapersonal, perspective taking) with different attentional foci (self, object). Compared to external mental locations, internal ones showed significantly increased alpha2 power, especially when the observer was focusing on an object. Alpha2 and beta2 were increased in the empathic condition compared to the extrapersonal perspective. Delta power was significantly higher when the attentional focus was directed towards an object in comparison to the participant’s own self. This exploratory study demonstrates highly significant differences between various mental locations and foci, suggesting that the proposed categories of mental location and intra- and interpersonal attentional foci are not only helpful theoretical concepts but are also physiologically relevant and therefore may relate to basic brain processing mechanisms.